Transposon based mutagenesis and mapping of transposon insertion sites within the Ehrlichia chaffeensis genome using semi random two-step PCR - Indukuri, Vijaya Varma (Kansas State University, 2013)
Ehrlichia chaffeensis a tick transmitted Anaplasmataceae family pathogen responsible for human monocytic ehrlichiosis. Differential gene expression appears to be an important pathogen adaptation mechanism for its survival in dual hosts. One of the ways to test this hypothesis is by performing mutational analysis that aids in altering the expression of genes. Mutagenesis is also a useful tool to study the effects of a gene function in an organism. Focus of my research has been to prepare several modified Himar transposon mutagenesis constructs for their value in introducing mutations in E. chaffeensis genome. While the work is in progress, research team from our group used existing Himar transposon mutagenesis plasmids and was able to create mutations in E. chaffeensis. Multiple mutations were identified by Southern blot analysis. I redirected my research efforts towards mapping the genomic insertion sites by performing the semi-random two step PCR (ST-PCR) method, followed by DNA sequence analysis. In this method, the first PCR is performed with genomic DNA as the template with a primer specific to the insertion segment and the second primer containing an anchored degenerate sequence segment. The product from the first PCR is used in the second PCR with nested transposon insertion primer and a primer designed to bind to the known sequence portion of degenerate primer segment. This method aided in identifying the genomic locations of four E. chaffeensis mutants and also was valuable in confirming four other sites mapped previously by the rescue cloning method. This is the first mutational analysis study in the genome of an Ehrlichia species. Mapping the genomic transposon insertion sites is the first critical step needed for the continued research to define the importance of the mutations in understanding the pathogenesis caused by the organism.
Keywords: Transposon mutagenesis; Mapping; Insertion mutations; Ehrlichia chaffeensis; Molecular Biology (0307)